POLA PENYELESAIAN SENGKETA TANAH ULAYAT DI SUMATERA BARAT (Sengketa antara Masyarakat dengan Investor) - Titin Fatimah; Hengki Andora (Jurnal Ilmu Hukum, 2014)
As other territories in Indonesia, theusing of communal land by privateenterprise has been also creatingdisputes in West Sumatra. Accordingto the law of land procurement inIndonesia, for getting land, a privateenterprise should contact the landowners (or traditional communities)as the subject of communal land formaking contract directly. As amatter of fact, they have got the landfrom the Local Government not fromthepeople.Thecommunitiesprotested to the corporate activitieson their land. Beside that, the privateenterprises have got agrement withcommunities, but they did not followit, for instance building plasmaplantation for the communities. Thecorporates have been doing disputessettlements, but it is not effisien tosolve the problem. The communitieshave also done everything forstruggling their land, such asnegotiation even into the court. But,they have not got their rights yet. Inthe field, it has involved poverty andenvironmental degradation.Keyword : dispute settlement